Comparative evaluation of different oil pulling agents and 0.2% chlorhexidine mouthwash as an adjunct to full-mouth scaling and root planing in plaque-induced gingivitis: A single-blind randomized control trial - Pallavi Vilas Bhalerao; Triveni Ashok Kale Bacchav; Swanpa Arunkumar Mahale; Amit Arvind Agrawal; Kunal Sethi; Tejashvi Ashok Seth (Wolters Kluwer Medknow Publications, 2024)
Introduction: Oil pulling is old Indian natural daily practice which has been written in Ayurveda texts such as Charak and Sushruta Samhita. The act of swishing oil around the mouth removes microbes. Therefore, oil pulling reduces plaque-induced gingivitis. Naturally occurring products like coconut oil and sesame oil are enriched with antimicrobial activity. These oils are cheaper and easily available. Therefore, the aim of this article is to compare the efficacy of coconut, sesame oil, and chlorhexidine mouthwash as an adjunct to full-mouth scaling and root planing (SRP) in patients with plaque-induced gingivitis. Aim and Objectives: This study aimed to compare the efficacy of coconut oil sesame oil and chlorhexidine mouthwash as an adjunct to SRP in patients with plaque-induced gingivitis. Materials and Methods: Sixty patients of plaque-induced gingivitis were randomly divided into four groups: SRP, coconut oil, sesame oil, and chlorhexidine mouthwash. Clinical measurements included plaque index, gingival index (GI), and simplified oral hygiene index at baseline, 7 days, 15 days, 1 month, and 3 months. Microbial analysis was carried out. Results: There was a significant reduction in plaque and gingival scores from baseline to 3 months for the chlorhexidine group. Intragroup comparison shows a statistically significant reduction in plaque and GI. Conclusion: Oil pulling considers to affect microbes to treat plaque-induced gingivitis.